THE ORGANIZATION OF PROFESSIONALLY ORIENTED ACTIONS AT FUTURE TEACHERS BY THE CURATOR - Vdovichenko, A.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The article touches upon the organization of professionally oriented activities for future teachers. The main functions of the curator of the student group in the conditions of pedagogical University are listed and the activity of the curator on the organization and attraction of students-future teachers to participation in professionally oriented events is described. Examples of the main activities carried out by the curators of future teachers-mathematicians in 1-2 courses at Saratov State University: curatorial hours, creative workshop, various competitions, student scientific conference, simulation modeling. These professionally oriented activities contribute to the entry of students into the professional educational space, further professional self-determination and are the basis for the stage of creative self-realization in senior courses. The obtained results can be used in the design and organization of the educational process in vocational education institutions.